Initial prediction of guided missile weight - Howe, D. (College of Aeronautics, 1957)
In the initial design stages of a guided missile it is essential tc predict the weight as accurately as is possible, and this note is intended to be a guide in this process. The information has been presented in a form which is applicable to two definite stages in the evaluation of the missile. These, for the sake of convenience, have been called the weapon system and project design stages, and correspond to the proc.adures of formulating the requirements for a particular missile and the initial interpretation of them. The note is intended to be as complete as is possible and the weight prediction methods suggested apply to equipment and systems as well as to structure. In some instances the formulae quoted are derived from published work, but much of the information is the result of original investigation. Whilst much of this investigation has been of an empirical nature, in some cases a theoretical approach has been used.